Development and validation of a nomogram for catheter-related thrombosis prediction in children with central venous catheter: a retrospective observational study - Wangfang Xie; Bin Xu; Xiaofang Lou; Jihua Zhu; Sheng Ye (BMC, 2024)
Abstract Background Catheter-related thrombosis (CRT) is a thrombotic complication associated with using central venous catheters (CVCs). Although risk factors for CRT were identified in children, no nomograms or predictive tools are available for the pediatric population with CVCs. This study aimed to develop and validate a prediction model of asymptomatic CRT in children with CVCs. Methods This retrospective observational study included consecutive pediatric patients who admitted to the Children's Hospital Zhejiang University School of Medicine and received CVCs between October and December 2021. Results This study included 669 patients, 553 (314 males, aged 22.00 [0.36, 180.00] months, 62 with CRT) were in the training set, and 116 (62 males, aged 15.00 [1.13, 156.00] months, 16 with CRT) were in the validation set. Multivariate logistic regression showed that a catheter time of 0-3 days (OR = 0.201, 95%CI: 0.081-0.497, P = 0.001), catheter time of 4-7 days (OR = 0.412, 95%CI: 0.176-0.964, P = 0.041), male (OR = 3.976, 95%CI: 1.864-4.483, P < 0.001), congenital heart diseases (OR = 0.277, 95%CI: 0.078-0.987, P = 0.048), postoperative (OR = 0.161, 95%CI: 0.072-0.360, P < 0.001), and femoral CVC (OR = 2.451, 95%CI: 1.129-5.318, P = 0.002) were independently associated with CRT. The nomogram incorporating these variables showed relatively good discrimination (AUC = 0.77, 95%CI: [0.65, 0.90]) and calibration abilities in the validation set, and the decision curve analysis (DCA) yielded a clinical net benefit. Conclusion A prediction model for CRT in children with CVC was established based on catheter time, sex, diseases, postoperative, and catheter vein. The nomogram based on logistic regression model showed favorable predictive performance.